Islamic principles in arts and design - Md. Sharif, Harlina; Hazumi, Hazman (IIUM Press, 2011)

(untitled)
The article Islamic Principles of Art and Design, attempt to address some of the issues regarding the terminology and the principles of Islamic art and architecture by making reference to Islam‖s core teachings and the products created throughout the history of its civilization. If we were to scrutinize the art or architectural history of the Muslim world, we would quickly realize that there is no evidence of any artist or patron in the fourteen centuries since the revelation of Islam who ever thought of his or her art as “Islamic.” In truth, the study of Islamic art and architecture, and the notion of a distinctively Islamic tradition of art and architecture, is a by-product of late nineteenth and early twentieth century Western scholarship. This all-embracing term “Islamic art or architecture” is an attempt to classify the multifaceted humanistic and spiritual expressions of the Muslim people, from lands stretching from Africa to the Atlantic, into a single palatable platform under the umbrella of “Islam”, at the expense of simplifying the cultural history of millions.